Blood donors' attitudes towards voluntary non‐remunerated donation in Trinidad and Tobago. Issue 4 (26th May 2017) - Charles, K. S.; Poon King, A.; Ramai, A.; Rajnath, K.; Ramkissoon, D.; Ramkissoon, S.; Ramlal, C.; Ramnarine, K.; Rampersad, K.; Legall, G.; Pooransingh, S.; Chantry, A. D.
SUMMARY: Objectives: To assess the attitude towards voluntary non‐remunerated blood donation among blood donors in Trinidad and Tobago (TRT). Background: Blood donors in TRT are either family replacement (F/R, 87%) or remunerated (13%). There is chronic blood shortage and high seroreactivity for transfusion‐transmissible infections (TTI) in donors. Converting existing to voluntary non‐remunerated donors (VNRD) reduces the need to recruit news donors in achieving 100% VNRD. Methods: A questionnaire‐based, cross‐sectional survey was conducted at two blood collection centres at an interval of 8 years. Donors were surveyed for sociodemographic characteristics, awareness of the blood shortage, previous donation behaviour, donor‐beneficiary linkage if F/R, willingness to become VNRD and choice of motivators for converting to VNRD. Results: A total of 400 and 595 donors respectively participated in Surveys 1 and 2, of whom 92·8 and 86·3% were F/R ( P  < 0·001), respectively. In both surveys, 52% of participants were unaware of an existing blood shortage ( P  = 0·983). Only 9·8 and 9·1% of participants expressed unwillingness to become VNRD ( P  = 0·720). The main motivators to convert to VNRD were reminders from the centre (84%) and extended opening hours (78%) in Survey 1 as compared to confidence that donated blood was used properly (73%) and shortened waiting times to donate (73%) in Survey 2. Conclusion: Despite low awareness of blood shortage, willingness to become VNRD was high among existing donors. Accountability and donor convenience underpinned the main motivators for converting to VNRD.